Defense Industry Policy Analysis Regarding Efforts To Increase Production Of Defense Equipment For National Security (Case Study At The Defense Industry Policy Committee) - Dwi Wahyudi; Bachtar Bakrie; Tina Rosa (Journal of Entrepreneur and Business, 2024)
Defense Industry Policy Committee (KKIP) is a Committee representing the Government to coordinate national policies in the planning, formulation, implementation, control, synchronization, and evaluation in the defense industry. The Government has made some policies related to human resources, pegembangan technology, collaboration, coaching, financing and marketing. In this study, researchers will focus on kebijakaan which has been made of the Government in the field of human resources, cooperation, Pembiayaaan and marketing. The purpose of this research is to know which policy is more dominant in the growing production tool national defence equipment. The researchers used a method of Analytical Hierarchy Process (AHP) to find a policy which is more dominant, conducting interviews with relevant parties. The results of this research show that the boost in production of defense equipment is the policy in terms of human resources which encompasses training/education, expertise and komptensi for penguasaaan defense industry technology. Key words: Defense Industry Policy, Analytical Hierarchy Process, Defense Industry Policy Committee (KKIP)